2009
DOI: 10.1016/s0034-7094(09)70084-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hemodynamic Changes in Acute Intoxication with Intravenous Bupivacaine and Ropivacaine in Swine

Abstract: In swine, ropivacaine caused less hemodynamic repercussions than bupivacaine when the same doses were administered intravenously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Intravascular bupivacaine injection may result in severe toxicity of the central nervous and cardiovascular systems 4 which are the main targets. Damage to the nervous system precedes cardiac compromise with signs and symptoms including tinnitus, metallic taste, visual disturbance, perioral numbness, loss of consciousness, convulsions and death.…”
Section: Introductionmentioning
confidence: 99%
“…Intravascular bupivacaine injection may result in severe toxicity of the central nervous and cardiovascular systems 4 which are the main targets. Damage to the nervous system precedes cardiac compromise with signs and symptoms including tinnitus, metallic taste, visual disturbance, perioral numbness, loss of consciousness, convulsions and death.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that bupivacaine results in a greater and more prolonged deleterious change in cardiac index, heart rate, and mean arterial pressure compared to ropivacaine. [ 19 ] Sub-group analysis studying the type of surgery and incidence of hypotension revealed a higher incidence in the bupivacaine group with mixed ‘author-defined’ surgeries (including lower abdominal, limb and gynaecology surgery), compared to the orthopaedic, major limb, arthroscopy and urology sub-group. [ 6 ] The reason could be that the required information size (IS) calculated using TSA was reached for the sub-group having mixed ‘author-defined’ surgeries including lower abdominal and limb/gynaecological procedures (n=324) compared to the orthopaedic/limb/arthroscopy sub-group (n=2414), thereby prompting us to conclude that more focussed RCTs are needed in the latter sub-group to conclude intrathecal ropivacaine's benefits over intrathecal bupivacaine for the latter sub-group.…”
Section: Discussionmentioning
confidence: 99%
“…Within this series, RVC has longer action than mepivacaine and is less toxic to the CNS/CVS than bupivacaine. Studies in pigs showed that RVC caused less hemodynamic repercussions than bupivacaine when equivalent doses were intravenously injected . Furthermore, studies in animals and humans suggest that RVC produces less motor block compared to bupivacaine, given its greater selectivity on the sensory nerve fibres, since it is synthesized and marketed in the S isomer form…”
Section: Introductionmentioning
confidence: 99%
“…Studies in pigs showed that RVC caused less hemodynamic repercussions than bupivacaine when equivalent doses were intravenously injected. [6] Furthermore, studies in animals and humans suggest that RVC produces less motor block compared to bupivacaine, given its greater selectivity on the sensory nerve fibres, [7] since it is synthesized and marketed in the S isomer form. [2] The use of sustained-release formulations has been proposed to improve solubility and bioavailability of low solubility anaesthetics, including systems based on cyclodextrins [8] and liposomal formulations.…”
Section: Introductionmentioning
confidence: 99%